The using of extract rabbits stomach in the making goat milk cheese ripened with Lactobacillus acidophylus - Sari, Inda Dewata (2010)
The aim of this research was to study the chemical physical quality of goat milk cheese that was made from extract rabbits stomach as coagulant and ripened with Lactobacillus acidophylus during 42 days. There are three groups of cheese ripening: 0 day, 21 days, and 42 days. The chemical qualities of milk chese were pH, acidity, free fatty acids, and water content, whereas the physical quality was texture or cheese hardness. The chemical and physical data was analized with completely randomized design. The result showed that ripening treatment has significant effect (P<0.05) on goat milk cheese acidity, free fatty acid, water content, and texture. During the day of 0, 21, and 42 ripening, the average of cheese acidity were 0.26%, 0.35%, 0.40%, free fatty acid were 1.32%, 2.28%, 2.23% 44.87%, water content were 42.10%, 39.10%, and texture were 62.07N, 120.21N, 312.52 N respectively. The pH of goat milk cheese was not affected by rippening treatment, and the average of pH was 5.85. In conclusion, goat milk cheese that was made from extract of rabbit stomach as coagulant and ripened with Lactobacillus acidophylus for 42 days was classified in hard cheese. There was increase of cheese acidity, free fatty acid and texture/hardness, whereas the water content decreased during ripening